An Analysis of Waqf Fundraising Strategies at Benteng Mikro Indonesia Sharia Cooperative - Casmita; Hendri Tanjung; Ibdalsyah (Al-Infaq Jurnal Ekonomi Islam, 2026)
Kopsyah BMI has a waqf program in the form of a project, waqf of 100 hectares of rice fields, hospitals, mosques, and Islamic schools. If 162,763 members waqf Rp. 1 million in a period of 1 year in installments or cash, then the potential acquisition of waqf funds is Rp. 162,763,000,000. In reality, waqf fundraising is not optimal. For this reason, it is necessary to know the problem factors, solutions, and strategies as well as the opinions of internal and external experts in collecting waqf funds at Kopsyah BMI. Using the Analytic Network Process (ANP) on 10 experts, the research results found problem factors, cooperative institutions (cooperative board), human resources (management commitment), products (absence of a waqf project blueprint). The solution is cooperative institutions (providing policies and assignments to members), human resources (conducting Training of Trainer (TOT) for employees), waqf products (compiling a waqf project blueprint). The strategy is to implement a weekly waqf movement, Training of Trainer (TOT) for members. The opinions of internal and external cooperative experts differ, namely the number of members (captive market) and the lack of understanding of members about waqf. It is expected that Kopsyah BMI in collecting waqf funds needs to make or provide policies and assignments to members to donate, conduct Training of Trainer (TOT) for employees, and compile a waqf project blueprint. The government and other institutions can provide support and always socialize waqf regulations and legislation, waqf education due to the lack of waqf literacy, and cooperation in waqf programs.